New Developments and Opportunities of Microbiota in Treating Breast Cancers - Meng, Zihui; Ye, Zixuan; Zhu, Pengrong; Zhu, Jianguo; Fang, Shuguang; Qiu, Tianzhu; Li, Yanan; Meng, Lijuan (Frontiers in Microbiology, 2022)
Despite the prevalence of breast cancer, over half of breast cancer cases are unknown to specific risk factors, which highlighted the importance to dig out more cancer-related factors. Currently, the microbiota has been proved to be a potent modulator of tumor environment in breast cancer which regulates the immune balance in tumor-related networks. Through a large amount of data accumulation, the microbiota has shown large possibilities to reveal more insights into the development or control of breast cancer. In order to expand the potential benefits of breast cancer patients, this review will discuss the distribution profile, the effect mechanism of breast cancer-related microbiota on tumor and further discussed its impact on different tumor therapies. Finally, we summarized the possibility of targeting microbiological therapies to improve breast cancer treatment or in combination with other therapies.